Perceptions and Controversies on Cholera in the Traditional Chinese Medicine Field in the Late Qing Dynasty - Shiqiang GUO; Haohuan WU; Yinghua WU; Zhiheng GUO (Wolters Kluwer Health/LWW, 2024)
Abstract. At the beginning of the initial cholera outbreak in China, Wang Qingren (王清任), after years of clinical trials, became an early representative who discovered the infectious characteristics and observed the course of cholera in the field of traditional Chinesse medicine (TCM). Kou Langao (寇兰皋) and Xu Zimo (徐子默), both medical practitioners, constructed a diagnosis and treatment system for cholera with cold patterns under the theory of typhoid. They represented "School of Cholera with Cold Patterns" (SCCP). In the 1860s, with the influence of Wang Shixiong's (王士雄) studies on the nature of cholera under the theory of epidemic febrile disease, the "School of Cholera with Heated Patterns" (SCHP) prevailed thereafter. The two schools complemented each other in theories and contributed to the integrity of TCM in cholera diagnosis and treatment. By reviewing previous literature, books, clinical cases, and historical materials in medical field, this article aims 1) to summarise the influence of TCM on the cognitive development towards cholera in the late Qing dynasty; 2) to explore the origin of the controversy between SCCP and SCHP from historical evidence; 3) to summarize the historical lessons from the debate over cholera in TCM based on the principle of treatment based on pattern identification, and offer suggestions for the current prevention and treatment of new diseases using TCM.